SCEENS' INFLUENCE ON DISTRIBURION OF PULSED MAGNETIC FIELD IN TRANSCRANIAL MAGNETIC STIMULATION - I. V. Samuilov; M. N. Kaidak; M. G. Saga; V. A. Belan (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article is devoted to an experimental test on the distribution of the pulse magnetic field’s range and how various screens influence it.